THE IMPLEMENTATION OF FORMATIVE ASSESSMENT ON STUDENT SPEAKING SKILLS DURING ONLINE LEARNING - Ni Ketut Yuni Sumaharani; Luh Putu Artini; Ni Nyoman Padmadewi Padmadewi (Journey: Journal of English Language and Pedagogy, 2023)
This study aims to analyse the teacher's perception of online formative assessment of student's speaking skills and to know the teacher's implementation of online formative assessment. This study used a mixed-method research approach. The subjects in this study were three English teachers at Mahasaraswati Denpasar University who implemented online formative assessments. The data was collected through observation, interviews via WhatsApp chat, and close-ended questionnaires. The result showed that the teacher positively perceived online formative assessmentregarding peer collaboration of student tests and enhancing test material. The teacher could help the students identify strengths and weaknesses in their speaking skills to improve their speaking performance. However, teachers have faced challenges in assessing online, such as students' ability to assess their attitude optimally, a lack of teacher technology knowledge, and time consumption when assessing numerous students. The study's implication is to provide teachers with an understanding of how to conduct formative speaking assessments in online classrooms without dismissing the character of formative assessment and preparation.